The effects of bicarbonated versus acetated Ringer's solutions on acid-base status and kidney injury following orthotopic liver transplantation: Protocol for a single-centre, randomised controlled trial (The BETTER trial) - Lv, Cheng; Zhou, Bin; Zhang, Donghua; Lin, Jiajia; Sun, Lingling; Zhang, Zhenzhen; Ding, Yuan; Sun, Rong; Zhang, Jie; Zhou, Chuyao; Zhang, Li; Wang, Xuan; et al. (Frontiers in Surgery, 2022)
Background The ideal crystalloid fluid of choice for fluid therapy during liver transplantation is unknown. Conventional balanced crystalloids are buffered with organic anions, which requires liver metabolism to prevent matabolic acidosis and protect renal function. Therefore they can not function properly during liver transplantation. On the contrary, the bicarbonated Ringer's solution (BRS) can maintain acid-base status regardless of liver function. In this study, we aimed to test the hypothesis that, in patients undergoing orthotopic liver transplantation, compared with acetated Ringer's solutions (ARS), perioperative fluid therapy with BRS could better maintain the acid-base status. Methods This is a prospective, single-centre, randomised controlled trial. 72 eligible patients will be randomised to receive either BRS or ARS perioperatively. The primary endpoint is the difference in standard base excess (SBE) before and after operation. Secondary endpoints include the incidence of acute kidney injury (AKI) within 48 h post operation and free and alive days to day 14 for intensive care admission, invasive ventilation, vasopressors, and renal replacement therapy (RRT). Discussion Metabolic acidosis is common perioperatively, potentially leading to decreased renal blood flow and reduced glomerular filtration rate. The use of balanced solutions can prevent hyperchloremic metabolic acidosis, thereby avoiding AKI in some patients. However, during liver transplantation, when well-functioning liver metabolism is lacking, the organic anions in conventional balanced solutions may remain strong anions and thus fail to maintain the acid-base status, but no solid clinical evidence exists now. This study will, for the first time, provide evidence on the relative effects of BRS vs. ARS on acid-base status and renal injury in patients undergoing liver transplantation. Clinical Trial Registration The trial has been registered at the Chinese Clinical Trials Registry (ChiCTR2100046889) on 29 May 2021.